Dietary acid load and markers of malnutrition, inflammation, and oxidative stress in hemodialysis patients - Balali, Arghavan; Nehls, Marilyn S.; Tabibi, Hadi; As’habi, Atefeh; Arab, Arman (Frontiers in Nutrition, 2024)
Aims: The present study was conducted to examine the association between dietary acid load (DAL) and markers of inflammation, oxidative stress, and malnutrition in a group of Iranian hemodialysis (HD) patients. Methods: This cross-sectional study was performed on individuals aged ≥18 years who were on HD at least 6 months before their enrollment in the study. A 4-day dietary recall was used for the evaluation of dietary intake. DAL was calculated using two methods including potential renal acid load (PRAL) and net endogenous acid production (NEAP). For assessing the malnutrition status, we used the subjective global assessment (SGA), dialysis malnutrition score (DMS), and malnutrition inflammation score (MIS). Overnight blood samples were collected from each participant to assess serum levels of high-sensitivity C-reactive protein (hs-CRP), soluble intercellular adhesion molecule-1 (sICAM-1), soluble vascular adhesion molecule-1 (sVCAM-1), sE-selectin, malondialdehyde (MDA), nitric oxide (NO), and endothelin-1. Results: In total, 291 patients with a mean age of 57.73±0.88 years and HD vintage of 4.27±0.25 months were enrolled in the current study. Significant positive associations were observed between PRAL and hs-CRP (β=1.77, 95% CI: 0.88, 2.65), sICAM-1 (β=83.21, 95% CI: 10.39, 156.04), sVCAM-1 (β=194.63, 95% CI: 74.68, 314.58), and sE-selectin (β=6.66, 95% CI: 1.81, 11.50) among participants with the highest PRAL scores, compared to those with the lowest PRAL scores. NEAP was positively correlated with hs-CRP (β=1.34, 95% CI: 0.46, 2.22), sICAM-1 (β=88.83, 95% CI: 16.99, 160.67), and MDA (β=0.35, 95% CI: 0.005, 0.71). Additionally, marginally significant higher odds of SGA (OR=1.98, 95% CI: 0.95, 4.11) and DMS (OR=1.94, 95% CI: 0.92, 4.05) were observed in individuals in the third tertile of PRAL vs. the first tertile of PRAL. NEAP had also a marginally significant positive correlation with DMS (OR=2.01, 95% CI: 0.93, 4.31). Conclusion: This study illustrates that higher consumption of acidic foods is correlated with markers of inflammation, oxidative stress, and malnutrition in HD patients.